Seroconversion rates after the second COVID-19 vaccination in patients with systemic light chain (AL) amyloidosis - Liebers, Nora; Schönland, Stefan; Speer, Claudius; Edelmann, Dominic; Schnitzler, Paul; Kräusslich, Hans-Georg; Müller-Tidow, Carsten; Hegenbart, Ute; Dietrich, Sascha (HemaSphere, 2022)
An abstract is unavailable.
Gesehen am 13.05.2022